Comparative Study of Bupivacaine-Fentanyl Versus Bupivacaine-Clonidine in Patients Undergoing Spinal Anaesthesia for Orthopedic Procedures - Chakraborty, Dr. Keya; Mandal, Dr. Uma; Porel, Dr. Swarbhanu; Patra, Dr Asis Kumar (International Journal of Innovative Research in Medical Science, 2022)
Background: There are many adjuvants used along with bupivacaine for subarachnoid block, but Fentanyl and Clonidine are commonly used as adjuvants to intrathecal bupivacaine for prolonging both sensory and motor blockade as well as postoperative analgesia in patients undergoing lower limb orthopedic surgery. Aim: The aim of the present study was to compare the effect of intrathecal Clonidine and Fentanyl as adjuvants to Bupivacaine in the subarachnoid block for lower limb orthopedic surgery. Materials and Methods: 200 patients belonging to American Society of Anaesthesiologists I or II, scheduled for lower limb orthopedic surgery under spinal anaesthesia were randomly allocated to one of the two following groups to receive Bupivacaine 15mg combined with 50